2002
DOI: 10.1113/jphysiol.2002.025866
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of NA+−CA2+ exchange is 3:1 in guinea‐pig ventricular myocytes

Abstract: In single guinea‐pig ventricular myocytes, we examined the stoichiometry of Na+‐Ca2+ exchange (NCX) by measuring the reversal potential (ENCX) of NCX current (INCX) and intracellular Ca2+ concentration ([Ca2+]i) with the whole‐cell voltage‐clamp technique and confocal microscopy, respectively. With given ionic concentrations in the external and pipette solutions, the predicted ENCX were −73 and −11 mV at 3:1 and 4:1 stoichiometries, respectively. ENCX measured were −69 ± 2 mV (n= 11), −47 ± 1 mV (n= 14) and −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…They found that eliminating external Na + to inhibit NHE induced a larger change in the Ca 2+ current due to a more profound change in pH. We also experienced that intracellular Na + concentration cannot be controlled when NCX is active (7). Therefore, although we did not demonstrate it experimentally in the present paper, it can be expected that under the present ionic conditions, activation of NHE could change intracellular pH and intracellular Na + concentration.…”
Section: Discussionmentioning
confidence: 56%
“…They found that eliminating external Na + to inhibit NHE induced a larger change in the Ca 2+ current due to a more profound change in pH. We also experienced that intracellular Na + concentration cannot be controlled when NCX is active (7). Therefore, although we did not demonstrate it experimentally in the present paper, it can be expected that under the present ionic conditions, activation of NHE could change intracellular pH and intracellular Na + concentration.…”
Section: Discussionmentioning
confidence: 56%
“…16 We generated ramp pulses to induce INa and ICa using a function generator (NF, Tokyo) as described previously. 17 AP was recorded at 10-s intervals using a K + -pipette solution and Tyrode external solution as described previously. 16 Ito was elicited by depolarizing square pulses of 200-ms duration to the voltage range between -40 mV and +60 mV with 10 mV steps from the holding potential of -40 mV.…”
Section: Whole-cell Patch-clamp Analysismentioning
confidence: 99%
“…This exchanger transports three Na + ions for one Ca 2+ ion, and is driven by the Ca 2+ and Na + gradients over the plasma membrane (1,2). In fact, Ca 2+ -dependent neurotransmitter release is affected by local Ca 2+ homeostasis according to NCX activity (3,4), thus NCX plays an important role in the intracellular Ca 2+ concentration, which represent a major event in many pathophysiologic processes.…”
Section: Introductionmentioning
confidence: 99%